Psychosocial work environment and leisure-time physical activity: the Stormont Study - Houdmont, Jonathan; Clemes, S.; Munir, F.; Wilson, K.; Kerr, Robert; Addley, Ken (Oxford University Press, 2015)
Background: Research findings are equivocal on relations between the psychosocial work environment and leisure-time physical activity (LTPA). This might be partly due to studies having focused on a restricted set of psychosocial dimensions, thereby failing to capture all relevant domains. Aims: First, to examine cross-sectional associations between seven psychosocial work environment domains and LTPA in a large sample of UK civil servants. Second, to profile LTPA and consider this in relation to UK government recommendations on physical activity.